2015
DOI: 10.1021/acsami.5b01988
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Switching and Polarization Reversal of Hydrothermal-Method-Grown Undoped Zinc Oxide Nanorods by Using Scanning Probe Microscopy Techniques

Abstract: This paper reports the localized electrical, polarization reversal, and piezoelectric properties of the individual hexagonal ZnO nanorods, which are grown via the hydrothermal method and textured with [0001] orientation. The studies are conducted with conductive atomic force microscopy (c-AFM) and piezoresponse force microscopy (PFM) techniques. The correlation between the resistance switching and polarization reversal is discussed. The c-AFM results show that there is less variation on the set or reset voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…In addition, the conducting regions of RRAM often generate high electric fields during module operation, disintegrating the region (Long et al, ). As shown in all current images in Figure , the conducting regions are distributed over the edge of the nanorod surface, because the charge accumulation forms a corona discharge‐like region (Beinik et al, ; Xiao, Ong, Guo, Ho, & Zeng, ). The coverage percentage of the conducting region on sample S 1 is as high as 46.6%, which severely limits the stability and lifetime of the RRAM module.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the conducting regions of RRAM often generate high electric fields during module operation, disintegrating the region (Long et al, ). As shown in all current images in Figure , the conducting regions are distributed over the edge of the nanorod surface, because the charge accumulation forms a corona discharge‐like region (Beinik et al, ; Xiao, Ong, Guo, Ho, & Zeng, ). The coverage percentage of the conducting region on sample S 1 is as high as 46.6%, which severely limits the stability and lifetime of the RRAM module.…”
Section: Resultsmentioning
confidence: 99%
“…These coupling behaviors may also influence each other, i.e., one coupling phenomenon may cause another coupling effect. For instance, when ZnO was switched to high resistance state by a large electric field, its polarization dipoles can be reversed by a smaller electric field in a similar way as the polarization switching characteristics in the traditional ferroelectric materials …”
Section: Multifield Coupling Phenomena Of Advanced Materialsmentioning
confidence: 89%
“…For instance, at a metal–semiconductor interface, charge injection due to highly localized electric field might cause the shift of Fermi level, hence changing the electrical conductance of the materials . Another example is ZnO, the external electric field might cause the reorientation of the dielectric dipoles, which affected the resistive switching behavior, and further initiated a polarization switching phenomenon similar to that of the ferroelectric materials …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that the conductivity in ZnO NR array devices can be exploited for the emulation of synaptic functions, since the device conductivity can be progressively modulated by means of voltage spike trains. [266,267] For practical resistive random access memory (RRAM or ReRAM) applications, Tseng et al [244] proposed the realization of resistive switching devices based on ZnO NR array/polymethylmethacrylate (PMMA) heterostructures. In this case, unipolar resistive switching was observed and attributed to a thermochemical mechanism (that is not polar dependent) of formation/rupture of a conductive filament of oxygen vacancies on the NW surface.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%